Ankyrin-mediated self-protection during cell invasion by the bacterial predator Bdellovibrio bacteriovorus - Lambert, Carey; Cadby, Ian; Till, Rob; Bui, Nhat Khai; Lerner, Thomas R.; Hughes, William S.; Lee, David J.; Alderwick, Luke J.; Vollmer, Waldemar; Sockett, R. Elizabeth; Lovering, Andrew L. (Nature Publishing Group, 2015)
Predatory Bdellovibrio bacteriovorus are natural antimicrobial organisms, killing other bacteria by whole-cell invasion. Self-protection against prey-metabolizing enzymes is important for the evolution of predation. Initial prey entry involves the predator’s peptidoglycan DD-endopeptidases, which decrosslink cell walls and prevent wasteful entry by a second predator. Here we identify and characterize a self-protection protein from B. bacteriovorus, Bd3460, which displays an ankyrin-based fold common to intracellular pathogens of eukaryotes. Co-crystal structures reveal Bd3460 complexation of dual targets, binding a conserved epitope of each of the Bd3459 and Bd0816 endopeptidases. Complexation inhibits endopeptidase activity and cell wall decrosslinking in vitro. Self-protection is vital — DBd3460 Bdellovibrio deleteriously decrosslink self-peptidoglycan upon invasion, adopt a round morpholog, and lose predatory capacity and cellular integrity. Our analysis provides the first mechanistic examination of self-protection in Bdellovibrio, documents protection-multiplicity for products of two different genomic loci, and reveals an important evolutionary adaptation to an invasive predatory bacterial lifestyle.